Design and simulation calculations for one - and two - neutron transfer ²⁴Si(p,d)²³Si and ²⁴Si(p,t)²²Si reaction experiment - N., T. Khai; B., D. Linh; L., X. Chung; D., T. Khoa; A. , Obertelli; A. , Corsi; A. , Gillibert; N. , Alamanos; D. , Sohler; Zs. , Dombradi; N. , Keeley (Nuclear Science and Technology, 2013)
Magic numbers are well established for stable nuclei: 2, 8, 20, 28, 50, 82, 126 but are known not to be valid for unstable neutron-rich and proton-rich nuclei located far from the β-stability region. Normally, structural research for these nuclei is performed based on inverse-kinematics nuclear reaction experiment with secondary radioactive isotope beams produced by the cyclotron facility. In this work we would like to report on the design and simulation calculations for an experiment on producing proton-rich isotopes 22-23Si based on one- and two-neutron transfer reactions of (p,d) and (p,t) types with 42 MeV/nucleon incident 24Si beam from the accelerator facility SPIRAL2 at GANIL, France. The obtained results are included: (i) optimization design for experimental configuration in inverse kinematics, (ii) tracking of beam trajectory with detectors CATS1&2, (iii) particle identification with MUST2 telescope system, (iv) identification for g.s and 2+ excited states, and (v) count statistics evaluation and reconstruction for nuclear excitation spectra. The main purposes of the experiment are to measure the energies of the neutron single particle and hole states in 23Si from 24Si(p,d) reaction to deduce the strength of the N=8 shell closure, and populate the excited states of the expected doubly-magic nucleus 22Si from 24Si(p,t) reaction to check the stability of the N=14 shell closure.